RNA sequence containing hexanucleotide AAUAAA directs efficient mRNA polyadenylation in vitro. - Manley, J L (1985)
To determine whether a specific nucleotide sequence is required to direct polyadenylation of a simian virus 40 early pre-mRNA in a soluble HeLa whole-cell lysate, we constructed a series of rearranged and deleted DNA templates, transcribed them in vitro, and determined whether the resultant RNAs could be polyadenylated when incubated in whole-cell lysate. When a 237-base-pair DNA fragment encoding the 3' end of the simian virus 40 early pre-mRNA was transferred to recombinant plasmids encoding RNAs that were not substrates for polyadenylation, the resultant RNAs could now be polyadenylated efficiently. In one case, the chimeric RNA was polyadenylated even more efficiently than was the original simian virus 40 early transcript. Analysis of the RNAs produced from the deletion mutant templates revealed that only RNAs containing at least one copy of the AAUAAA sequence situated near the 3' end and implicated in 3'-end formation and polyadenylation in vivo could be polyadenylated in vitro. Surprisingly, this sequence directed polyadenylation of pre-mRNAs not only when near the RNA 3' end, i.e., 50 nucleotides or less away, but also when the 3' end was situated over 400 nucleotides downstream. Thus, our results show that a polyadenylic acid polymerase activity in HeLa lysates can recognize a specific nucleotide sequence in pre-mRNA and then, in the absence of the nucleolytic cleavage that presumably occurs in vivo, locate the RNA 3' end and use it as a primer for polyadenylic acid synthesis.